Are Pediatric Providers On-Board With Current Recommendations Related to Maternal Mental Health Screening at Well-Child Visits in the State of Georgia?. (November 2022) - Barrow, Kaitlyn; McGreal, Analise; LiVecche, Dillon; Van Cleve, Susan; Sikes, Chris; Buoli, Massimiliano; Serati, Marta; Bridges, Christy C.; Ezeamama, Amara; Barkin, Jennifer L.
BACKGROUND: The American Academy of Pediatrics (AAP) recommends that pediatric providers screen mothers for postpartum depression at the 1-, 2-, 4-, and 6-month well-child visits. However, compliance with this recommendation varies greatly and is far from 100%. This is significant, as perinatal mood and anxiety disorders (PMADs) represent the most common complication of childbearing. AIMS: This investigation was conducted to explore barriers to screening in the pediatric setting, reported advantages of screening, providers' knowledge of mental health supports in the community, and commonly observed (and explicitly stated) mental health issues in new mothers. All data collection took place in the state of Georgia, which has the worst rates of maternal mortality and morbidity in the United States. METHODS: A convenience sample of five pediatric practices was selected through the Mercer University School of Medicine's community preceptor network. All clinical staff at each site participated in one of five focus groups for a total of 31 participants. The conversations were audio-taped, transcribed, and thematically analyzed. RESULTS: Providers from two practices were formally screening for Postpartum Depression; they indicated that it added value to their practice. Those not screening cited several barriers including lack of time, training, and access to the mother's medical records. Several clinicians asserted that they were not trained to address mental health issues in their pediatric patients' mothers and that it was out of their realm of expertise. CONCLUSIONS: Provider compliance with the current AAP recommendations may increase with mandatory, specialized training in recognizing and treating PMADs.